Determinasi Teknologi Komunikasi Dan Tutupnya Media Sosial Path - Febriana, Ajeng Iva Dwi (LONTAR: Jurnal Ilmu Komunikasi, 2018)
The focus of this research is the influence of communication technology on the existence of social media. Determinism of technology makes humans as objects of technology itself which shapes humans both in terms of thinking, opinion and acting in a society. As a new media, online media and social media are required to continuously present the speed of information and make the audience able to easily interact with anyone and with anything. The novelty of features and the speed of information in social media (social networking) become a benchmark for the existence of social media. The closure of Path's social media services because social media cannot meet the needs of its users and the lack of new features in the application so that users are limited in accessing what information will be consumed and the loss of private space for social media users Path makes Path slowly begin abandoned by its users because it is considered to have no advantage anymore.Keywords: Determinism of Technology, Existence, Social Media